Elucidating a Muslim scholar's speech skills throughdigital storytelling: a qualitative content analysis / Rofiza Aboo Bakar - Aboo Bakar, Rofiza (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
In the globalized era, Muslim scholars use digital storytelling to talk about situational issues. With millions of social media followers, they are deemed influential. However, studies to understand their speech skills are too scarce, although they deal with communication the most. The aim of this paper is twofold. First, it aimed at understanding the speech skills employed by a Muslim scholar chosen as one of the World's 500 Most Influential Muslims in the year 2020. Secondly, it aimed at exploring the advice put forth by him about the issue of the COVID-19 pandemic. This study used a qualitative content analysis with the directed approach research design. A purposive sample of an influential Muslim scholar was selected. The data source was his digital story posted on YouTube about the COVID-19 issue. The findings indicated that he had utilized a repertoire of speech skills, such as soft conversational tone, easily comprehended words, clear narration and being respectful of the audience. The advice delineated was to remind all that everyone is equal, with death being the greatest equalizer, all possessions are only temporary, and submission to Allah in both good and bad times is unsurpassed. The speech skills may provide a useful point for class practitioners who wish to provide some guidance for their students about communication techniques. The advice may relieve the restlessness felt by many while fighting the invisible but threatening COVID-19 pandemic.